Factors affecting the adoption of green prevention and control techniques by family farms: Evidence from Henan province of China - Chen, Tingting; Lu, Xiaojing; Wu, Zhanyong (Frontiers in Psychology, 2022)
Encouraging farmers to adopt green prevention and control techniques (GCTs) is conducive to ensuring the quality and safety of agricultural products, the ecological environment and agricultural production. To explore the factors influencing vegetable farmers' adoption of GCTs, this study utilized the "information-motivation-behavior" intervention (IMB) model and ordered logistic model to empirically study the adoption behavior of 653 vegetable farmers in Henan Province, China. Our findings show that the IMB model significantly predicted farmers' adoption of GCTs. First, from the perspective of adoption decisions, 88.82% of the farmers have adopted GCTs, but the degree of adoption is low. Furthermore, the farmers' adoption of the GCTs model specifies that higher levels of GCTs information, motivation, and behavioral skills should result in a greater likelihood of engaging in GCTs adoption behavior. Moreover, motivation and behavioral skills are activated through information. In addition, this study verified the significant positive correlation between GCTs information, motivation, and behavioral skills, indicating that the theoretical framework of the IMB is applicable for the study of vegetable farmers’ behavior. The results of this study support the need for the government to promote the use of GCTs for vegetable pest control, as well as advance integrated prevention and control in the agricultural industry. Government policies should expand farmers’ access to GCTs information, increase the relevant agricultural subsidies and reduce the short-term costs and risks borne by farmers in adopting GCTs. Moreover, it is recommended to deepen the reform of agricultural technology promotion and pay attention to agricultural skills training for farmers.